KELAYAKAN PENGEMBANGAN BAHAN AJAR DIGITAL FLIPBOOK PADA PEMBELAJARAN BAHASA JEPANG SMA DI MALANG - Wiranto Aji Dewandono; Ulfah Sutiyarti (Jurnal Pendidikan Bahasa Jepang Undiksha, 2022)
Japanese is a unique language. Because most of the vocabulary uses vowels, namely a, i, u, e, and o, Japanese is considered interesting to learn because of this uniqueness. There are so many Japanese books or teaching materials circulating only in the form of physical books, but they are rarely found in digital format, especially flipbooks. From the needs analysis, it can be concluded that Japanese high school teachers in Malang need digital teaching materials that are easily accessible to all students. The method used in this research is Research and Development with a 4D development model (Define, Design, Develop, Disseminate) developed by Thiagarajan. This development produces a digital teaching material product based on flipbooks that are by the process and quality as indicated by validation by media and material experts with firm response criteria so that it is feasible to use.